ANALYSIS OF COMMON SIZE PROFIT AND LOSS STATEMENTS PT. SIANTAR TOP PERIOD 2020-2021 - Muhammad Zahrul Fuadi; Jorgeo O. Brusa; Rico Nur Ilham; Irada Sinta (PT. Radja Intercontinental Publishing, 2022)
Financial statements are the end result of the accounting cycle that is used as a tool to find out how the company is performing and can also be used as a reference for decision making. This study aims to determine the financial performance of PT. Siantar Top, Tbk, which refers to the income statement for the year 2020-2021 using the common size analysis method. This research is a descriptive type of research with a quantitative approach. The results showed that there was a drastic increase and decrease in several posts. Some of the reasons are that during 2020-2021 the world was hit by a pandemic so that it had an impact on the company's performance. Although the profit in 2021 was not better than 2020, the company was able to reach its expected target. This shows that the company's ability to sell is still quite good.